2010
DOI: 10.1016/j.devcel.2010.07.017
|View full text |Cite
|
Sign up to set email alerts
|

BMP Signals Promote Proepicardial Protrusion Necessary for Recruitment of Coronary Vessel and Epicardial Progenitors to the Heart

Abstract: SUMMARY The coronary vessels and epicardium arise from an extracardiac rudiment called the proepicardium. Failed fusion of the proepicardium to the heart results in severe coronary and heart defects. However, it is unknown how the proepicardium protrudes toward and attaches to the looping heart tube. Here we show that ectopic expression of BMP ligands in the embryonic myocardium can cause proepicardial cells to target aberrant regions of the heart. Additionally, misexpression of a BMP antagonist, Noggin, suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 78 publications
1
98
2
Order By: Relevance
“…30 Increased Bmpdependent signaling in RBPJk mutants was deduced on the basis of higher nuclear p-Smad 1/5/8 expression in the proepicardium and associated PM, and indicated that Bmp2 activity was expanded to the entire inflow region. Ectopic muscular differentiation at the venous pole of the heart in RBPJk mutants, revealed by the expression of cardiomyogenic markers such as Tpm1, ␣-SMA, cardiac troponin T, and cardiac actin suggests that muscularization of the SV horns had occurred prematurely.…”
Section: Notch Signaling Inactivation Alters CI Differentiation By Inmentioning
confidence: 99%
“…30 Increased Bmpdependent signaling in RBPJk mutants was deduced on the basis of higher nuclear p-Smad 1/5/8 expression in the proepicardium and associated PM, and indicated that Bmp2 activity was expanded to the entire inflow region. Ectopic muscular differentiation at the venous pole of the heart in RBPJk mutants, revealed by the expression of cardiomyogenic markers such as Tpm1, ␣-SMA, cardiac troponin T, and cardiac actin suggests that muscularization of the SV horns had occurred prematurely.…”
Section: Notch Signaling Inactivation Alters CI Differentiation By Inmentioning
confidence: 99%
“…This structure extends many tissue processes and covers the surface of the naked myocardium of the looped heart in avian species (Hiruma and Hirakow, 1989;Ho and Shimada, 1978;Viragh and Challice, 1981). Bone Morphogenetic Protein (BMP) has been identified as a factor that may be involved in controlling the timing and direction of proepicardial protrusion towards the heart (Ishii et al, 2010). The transcription factor GATA4 has been found to be strongly expressed in the proepicardium and is required for the formation of the epicardium (Watt et al, 2004).…”
Section: Development Of Coronary Vesselsmentioning
confidence: 99%
“…The results of ectopic Bmp2 expression in chicken myocardium suggest a model in which Bmps (presumably Bmp2 and Bmp4) expressed in the atrioventricular (AV) canal direct PE protrusion toward the heart tube. 30 In mammals, the predominant mode of PE cell transfer to the heart seems to be the release of PE cell cysts to the pericardial cavity, with the PE connecting to the heart relatively late in epicardial development. 3,4 Once PE cells adhere to the myocardial surface, they flatten and spread to form a characteristic cobblestone epithelial monolayer ( Figure 3A).…”
Section: Formation Of the Epicardium And Its Spreading Over The Myocamentioning
confidence: 99%
“…29 In addition, Bmp2 expression is crucial for attachment of PE cells to the heart. 30 All these events require highly patterned expression of Bmp2 in the PE/septum transversum region. 31 Bmps thus can be postulated to play a role in establishing the posteriormost myocardial limit (venous pole) of the developing heart.…”
Section: Signals Involved In Pe Specificationmentioning
confidence: 99%